STUDY E3 SUMO-PROTEIN LIGASE (NSMCE2) ,LIPID PROFILE ANDMALONDIALDEHYDE IN PATIENTS WITH ATHEROSCLEROSIS - WESEN A. MEHDI,; NAGHAM A. JASIM, (International Journal of Pharma and Bio Sciences, 2014)
The present work includes a clinical study of the E3 Sumo-Protein Ligase enzyme[NSMCE2] in 60 clinically diagnostic atherosclerosis patients compared with30 healthy as controls, alsothis study committed to the measurement several parameters levels such as lipid profile, MDA and relationship to E3 Sumo-Protein Ligase, the results observed that the serum triglyceride, total cholesterol, LDL, VLDL and LDL/HDL ratio showed significant increase in patients group in comparison to control group, while HDL showed significant decrease in patients group in comparison to control group.The level of malondialdehyde(MDA) were significant increase (p<0.001) in patients group in comparison to control group. The level of NSMCE2were highly Significant increase (p<0.0001) in patients group in comparison to healthy control group. The aim of the present study is to investigate the E3 Sumo-Protein Ligaseand some biochemical parameters in patients with atherosclerosis compared with control.